Initial growth of jatropha seedlings grown in soils of different textures - Sousa, Kidyaveline Lacerda de (2018)
Jatropha curcas L. is an oleaginous plant that presents high potential for biofuel production, but little is known about the cultivation techniques of this species, mainly in relation to the production of quality seedlings, which leads to high survival rates in the field. The objective of this work was to evaluate the performance of young Jatropha curcas plants cultivated in soils with different textures under controlled conditions of greenhouse conditions in the municipality of Patos, Paraíba. The effects of five substrate compositions (treatments) were evaluated: 100% river sand; 100% clay soil material; 50% river sand + clay soil material 50%; 75% river sand + 25% clay soil material; 25% river sand + 75% clay soil material. The treatments were distributed in a completely randomized design with five replications. Plant height, stem diameter, leaf area, number of leaves and dry mass of roots and shoot were determined. The results of the present study show that young jatropha plants respond differently to soil texture variation; in general, important parameters such as stem diameter and shoot dry mass showed some sensitivity to the substrate with more clay. Considering a positive effect for most of the evaluated parameters, the substrate composed of 75% clay soil material and 25% river sand was the one that provided seedlings with better quality.